Brody's ghost. Book 2 - Crilley, Mark (Dark Horse ; Diamond [distributor], 2011)
"Brody knew that being mixed up with Talia, a dead girl turned ghost, was going to change his life forever. He just didn't realize it was going to involve going head to head with one of the most vicious gangs in the whole city. But here he was, giving himself over to the bizarre training methods of Kagemura, an ancient samurai ghost, to transform himself from a flabby slacker to a peak--condition fighter capable of bringing the city's most dangerous criminals to their knees"--P. [4] of cover.